Realization of a fast-response flexible ultraviolet photodetector employing a metal–semiconductor–metal structure InGaZnO photodiode. Issue 107 (16th October 2015) - Zhou, H. T.; Li, L.; Chen, H. Y.; Guo, Z.; Jiao, S. J.; Sun, W. J.
Abstract : A flexible UV photodetector (PD) has been fabricated based on the amorphous InGaZnO film. It shows good photoresponse characteristics before and after bending, and fast response speed compared with the most reported flexible UV PDs. Abstract : Amorphous InGaZnO (a-IGZO) thin films have been grown on polyethylene terephthalate (PET) substrates using a plasma-assisted pulsed laser deposition (PLD) technique, and a flexible ultraviolet (UV) photodetector (PD) with a simple metal–semiconductor–metal (MSM) structure was prepared on the a-IGZO films. The flexible PD shows relatively good photoresponse characteristics before and after bending, and retains good folding reproducibility after repeated bending up to 500 cycles. More importantly, it shows a fast speed with response and recovery times of 0.8 ms and 2.0 ms, 33.8 ms, which are much faster than that of the reported flexible ultraviolet detectors. The devices reported in this paper provide an optimal way to realize flexible ultraviolet detectors with fast speed.